Modification of the SERS spectrum of cyanide traces due to complex formation between cyanide and silver. (6th June 2018) - Dao, Tran Cao; Kieu, Ngoc Minh; Luong, Truc Quynh Ngan; Cao, Tuan Anh; Nguyen, Ngoc Hai; Le, Van Vu
Abstract: It is well known that cyanide is an extremely toxic lethal poison with human death within minutes after exposure to only 300 ppm cyanide. On the other hand, cyanide is released into the environment (mainly through waste water) every day from various human activities. Therefore, rapid, sensitive and cost-effective cyanide trace detection is an urgent need. Surface-enhanced Raman scattering (SERS) is a method that meets these requirements. It should be noted, however, that in this technique SERS substrates, which are usually made of gold or silver, will be leached with aqueous cyanide by the formation of complexes between gold or silver with cyanide. This will cause the SERS spectrum of cyanide to be modified. When determining cyanide concentrations by SERS analysis, this spectral modification should be taken into account. This report presents the SERS spectral modification of aqueous cyanide traces (in ppm and lower concentration range) when the SERS substrates used are flower-like silver micro-structures.